The Influence of Cochlear Implant-Based Electric Stimulation on the Electrophysiological Characteristics of Cultured Spiral Ganglion Neurons - Na Shen; Lei Zhou; Bin Lai; Shufeng Li (Neural Plasticity)
Background. Cochlear implant-based electrical stimulation may be an important reason to induce the residual hearing loss after cochlear implantation. In our previous study, we found that charge-balanced biphasic electrical stimulation inhibited the neurite growth of spiral ganglion neurons (SGNs) and decreased Schwann cell density in vitro. In this study, we want to know whether cochlear implant-based electrical stimulation can induce the change of electrical activity in cultured SGNs. Methods. Spiral ganglion neuron electrical stimulation in vitro model is established using the devices delivering cochlear implant-based electrical stimulation. After 48 h treatment by 50 μA or 100 μA electrical stimulation, the action potential (AP) and voltage depended calcium current (ICa) of SGNs are recorded using whole-cell electrophysiological method. Results. The results show that the ICa of SGNs is decreased significantly in 50 μA and 100 μA electrical stimulation groups. The reversal potential of ICa is nearly +80 mV in control SGN, but the reversal potential decreases to +50 mV in 50 μA and 100 μA electrical stimulation groups. Interestingly, the AP amplitude, the AP latency, and the AP duration of SGNs have no statistically significant differences in all three groups. Conclusion. Our study suggests cochlear implant-based electrical stimulation only significantly inhibit the ICa of cultured SGNs but has no effect on the firing of AP, and the relation of ICa inhibition and SGN damage induced by electrical stimulation and its mechanism needs to be further studied.